Psikoterapi Abū Naṣr al-Sarrāj al-Ṭūsī: Tinjauan atas al-Maqāmāt al-Rūḥāniyyah dalam Kitab al- Luma‘ - Muhammad Valiyyul Haqq (Jurnal Penelitian Ilmu Ushuluddin, 2021)
Appeared for the first time in 1965 in the monumental work of Reza Arasteh, Sufi spiritual approaches and methods in psychotherapy have to wait for Muslim scholars attention in the 21st century. To our concern, up to now only few studies which dive in the ocean of Sufi doctrinal aspects of psychotherapy: most of them still swim at the upper level trying to estimate the possible relationship between Sufi spiritual practices and methods of psychotherapy. However, to our surprise, none of these few studies that focus on the Sufi spiritual maqāmāt, the well-known meticulous step-by-step guidance for those who want to master their soul and mental states. In the absence of this, the present article attempts to explore the maqāmāt discussed by Abū al-Naṣr al-Sarrāj al-Ṭūsī in his famous al-Luma‘ in light of psychotherapy. At the end this article finds that these Sufi maqāmāt are not only means for spiritual purification, i.e., soul and mental well-being, but also al-Sarrāj’s model of Sufistic psychotherapeutic outline method.